2021
DOI: 10.22141/2312-413x.8.3-4.2020.212657
|View full text |Cite
|
Sign up to set email alerts
|

Применение пробиотического штамма Streptococcus salivarius К12 в лечении острых тонзиллофарингитов у детей

Abstract: Застосування пробіотичного штаму Streptococcus salivarius K12 у лікуванні гострих тонзилофарингітів у дітей Резюме. У статті висвітлено дослідження ефективності застосування штаму Streptococcus salivarius K12 у лікуванні гострих тонзилофарингітів у дітей. Під спостереженням перебувало 50 дітей віком від 2 до 17 років із діагнозом гострого стрептококового тонзилофарингіту, з яких 25 становили основну групу й отримували в комплексному лікуванні Streptococcus salivarius K12 (препарат Бактобліс). Також у роботі по… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Besides the action mode of salivaricins described previously, a well-maintained oropharynx homeostasis status also helps keeping the human host tolerant of respiratory tract infections. Previous studies have demonstrated that the use of oropharyngeal probiotic as part of the complex therapy of recurrent tonsillitis for 30 days was characterized by a rapid relief of both local and general manifestations of recurrent tonsillitis, as well as a significant improvement in the microflora of the upper respiratory tract ( Ilchenko et al, 2020 ; Kramarev et al, 2020 ). It is noted that in the control group, the incidence rate of respiratory tract infections increased linearly until the 20th day and seemed to slow down in the last 10 days during this trial, which may be explained by the fact that the number of hospitalized COVID-19 patients gradually decreased after they were cured and left the hospitals and the relief of COVID-19 pandemic in Wuhan area, thus relieved the shortage of medical resources during the emergence of the outbreak which caused extremely stressful work schedule and which also made the medical staff experience a lower immunity during the period of medical resource shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the action mode of salivaricins described previously, a well-maintained oropharynx homeostasis status also helps keeping the human host tolerant of respiratory tract infections. Previous studies have demonstrated that the use of oropharyngeal probiotic as part of the complex therapy of recurrent tonsillitis for 30 days was characterized by a rapid relief of both local and general manifestations of recurrent tonsillitis, as well as a significant improvement in the microflora of the upper respiratory tract ( Ilchenko et al, 2020 ; Kramarev et al, 2020 ). It is noted that in the control group, the incidence rate of respiratory tract infections increased linearly until the 20th day and seemed to slow down in the last 10 days during this trial, which may be explained by the fact that the number of hospitalized COVID-19 patients gradually decreased after they were cured and left the hospitals and the relief of COVID-19 pandemic in Wuhan area, thus relieved the shortage of medical resources during the emergence of the outbreak which caused extremely stressful work schedule and which also made the medical staff experience a lower immunity during the period of medical resource shortage.…”
Section: Discussionmentioning
confidence: 99%